A critical analysis of the structural dynamics operative within the Baptist Union of Southern Africa (BUSA) from 1960-2005 and an evaluation of these dynamics in the light of BUSA ecclesiology - Vos, C.J.A. (Casparus Johannes Adam), 1945- (University of Pretoria, 2013)
Dissertation (MA(Theology))--University of Pretoria, 2009.